Increasing trends of lung cancer in Golestan province, Northern Iran (2004–2016). (April 2020) - Salamat, Faezeh; Khandashpour, Mahmoud; Naeimi-Tabiei, Mohammad; Ariannia, Ali; Ashaari, Mohammad; Sedaghat, SeyedMehdi; Ghasemi-Kebria, Fatemeh; Salamat, Fatemeh; Moghaddami, Abbas; Hasanpour-Heidari, Susan; Hoseinpour, Reza; Jafari-Delouei, Nastaran; et al.
Highlights: Golestan province, Iran is a high-risk area for esophageal cancer and tuberculosis (TB). We presented trends and distribution of lung cancer (LC) in Golestan, during 2004-2016. We found high rates and significant increasing trends in incidence of LC in Golestan. The trends were more prominent in rural area and hot points were found in western part. Further studies are needed to clarify the role of TB and other risk factors on LC burden. Abstract: Introduction: We aimed to present the time trends and geographical distribution of lung cancer in Golestan province, a high-risk area for pulmonary tuberculosis (TB) in Northern Iran (2004-2016). Methods: Data on incident primary lung cancers were obtained from the Golestan population-based cancer registry. The data were analyzed by CanReg-5 software to calculate the age-standardized incidence rates (ASRs). We used Joinpoint software for time trend analysis. Average annual percent changes were calculated. The contribution of population aging, population growth and risk to the overall changes in incidence of lung cancer were determined using partitioning analysis. Results: Overall, 1829 cases of lung cancer were registered by the GPCR during 2004-2016, of which 1274 (69.7%, ASR in 2016 = 21.3) were men and 555 (30.3%, ASR in 2016 = 11.4) were women. The results of Joinpoint regression suggested a significant increasing trend in incidence of lung cancer in Golestan province during 2004 and 2016 (AAPC = 3.74; p-value = 0.01) with more prominent increasing in rural population (AAPC = 4.93; p-value<0.01). The number of new cases of lung cancer increased by 131.6% (from 98 in 2004 to 227 in 2016), of which 34.1%, 22.3% and 75.3% were due to population size, population aging and risk, respectively. Hot points of lung cancer were found in western parts of the Golestan. Conclusion: With high incidence rates and increasing trends of lung cancer, further studies are warranted to clarify the role of TB and other risk factors on its burden in this population.